Odpowiedzi

2009-09-07T19:49:31+02:00
Podstawiasz z "x" wskazaną liczbę:
a) (16 -20 + 8) : (16 + 2) = (-4 +8): 18 = 2/9
b) 3/2 * (-2/3) + [√(-4/3 - 3)²] : (-2)+1 = -1 + √(-13/3)² = -1 +√169/9 = -1 + 13/3 = 10/3
d) [√2/2 + 4 - 4(2√2 + 1)] : [(3√2/2 - 2)² - (√2 + 3)² = [(√2 + 8)/2 - 8√2 - 4] : [(3√2 -4)²/4 - (2 + 6√2 + 9) = [(√2 + 8 - 16√2 - 8)/2] * [4/(18 - 24√2 + 16 - 44 - 24√2)] = (-15√2 / 2) * [4 / (-10 - 48√2)] = (-30√2) / (-10 -48√2) = 15√2 / (5+24√2)
Coś w tym stylu, mam nadzieję, że nie zrobiłam błędu